Pendampingan Tata Kelola Sistem Informasi Desa Berbasis Website Desa Linggo Kecamatan Kejayan Kabupaten Pasuruan - Rosyidi, Khafizh; Khoiron, M.; Huda, M. Fathul; Umar, Saiful; Nafi’udin, M. Badrun (Humanist Journal, 2022)
The website-based Village Information System is the best alternative in seeking public information disclosure for the Village Government. Websites are now the most relevant media to be used as information channels among village millennials. The Village website can provide various information about the profile and activities of the government and the community in the village environment. Apart from being a promotional media, the Linggo Village Website also displays other important information needed by the community. This website-based Village Information System can also be a source of information for the wider community in finding the main source of information to avoid hoaxes on identical information related to Linggo Village circulating on other website channels. This Village Information System governance assistance is an effort to increase the capacity of Linggo Village operators in managing the website. Meanwhile, the Linggo Village website was deliberately built as a source of public information based on the principle of public information disclosure.